Temporal data and the relational model a detailed investigation into the application of interval and relation theory to the problem of temporal database management - Date, C. J.; Darwen, Hugh.; Lorentzos, Nikos A. (San Diego, CA : Morgan Kaufmann Publishers, 2003)
Temporal database systems are systems that provide special support for storing, querying, and updating historical and/or future data. Current DBMSs provide essentially no temporal features at all, but this situation is likely to change soon for a variety of reasons; in fact, temporal databases are virtually certain to become important sooner rather than later, in the commercial world as well as in academia. This book provides an in-depth description of the foundations and principles on which those temporal DBMSs will be built. These foundations and principles are firmly rooted in the relational model of data; thus, they represent an evolutionary step, not a revolutionary one, and they will stand the test of time. This book is arranged in three parts and a set of appendixes: * Preliminaries: Provides a detailed review of the relational model, and an overview of the Tutorial D language. * Laying the Foundations: Explains basic temporal data problems and introduces fundamental constructs and operators for addressing those problems. * Building on the Foundations: Applies the material of the previous part to issues of temporal database design, temporal constraints, temporal query and update, and much more. * Appendixes: Include annotated references and bibliography, implementation considerations, and other topics. Key features: * Describes a truly relational approach to the temporal data problem. * Addresses implementation as well as model issues. * Covers recent research on new database design techniques, a new normal form, new relational operators, new update operators, a new approach to the problem of "granularity," support for "cyclic point types," and other matters. * Includes review questions and exercises in every chapter. * Suitable for both reference and tutorial purposes.
A review of relational concepts -- An overview of Tutorial D -- Time and the database -- What is the problem? -- Intervals -- Operators on intervals -- The EXPAND and COLLAPSE operators -- The PACK and UNPACK operators -- Generalizing the relational operators -- Database design -- Integrity constraints 1 : candidate keys and related constraints -- Integrity constraints 2 : general constraints -- Database queries -- Database updates -- Stated times and logged times -- Point and interval types revisited.
Includes bibliographical references and index.
Keywords: Database management; Relational databases; Electronic books